PECULIARITIES OF LEGAL REGULATION OF HUMAN RIGHTS IN A PANDEMIC CONDITION - Ямненко, Тетяна Михайлівна; Стешенко, Марина Віталіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to explore the fundamental principles that are based on respect for human dignity and human rights and should guide the decision-making and practice of medicine in the current crisis. Research methods: general philosophical, general scientific and special legal methods, in particular dialectical method, method of analysis, system-functional method, formal-logical method, hermeneutic method. Results: generalized main methods and means of protecting the rights of patients in a pandemic COVID-19. Discussion: the convention requires equal access to health care for all people with limited resources so that the most vulnerable are not discriminated against; the data collected to combat COVID-19 must be securely protected; restrictions on human rights must be regulated by law and aimed at protecting the collective interests and public health; the rights of those involved in the development of therapeutic measures in times of crisis need special protection. Medical care should be available to everyone. This means that states must work with all stakeholders (including pharmaceutical companies) to achieve this goal, provided that this process is based on respect for human rights. In accordance with international standards for the observance of the right to health, medicines, institutions and services, including access to treatment and future vaccines and drugs against coronavirus, should be available in sufficient quantities for all, especially for the most vulnerable and disadvantaged groups. population that should have access to them. In the difficult times of the crisis in the health care system we are facing now, international cooperation and solidarity are crucial. Governments with economic and technical capabilities should help those who have fewer resources to prepare for and overcome the outbreak. States should also provide other States and international organizations with up-to-date information on the level and consequences of the spread of coronavirus at the national level and information on possible coronavirus treatment that they have.